2022
DOI: 10.1186/s13256-022-03433-4
|View full text |Cite
|
Sign up to set email alerts
|

Superficial spreading cervical squamous cell carcinoma in situ involving the endometrium: a case report and review of the literature

Abstract: Background The spread of cervical squamous cell carcinoma to the inner surface of the uterus with replacement of the endometrium is rare. Continuity of the lesion must be demonstrated to confirm superficial spread and rule out concomitant endometrial cancer. Case presentation We present the case of a 66-year-old white woman with superficial spreading squamous cell carcinoma of the cervix that involved the endometrium. Her relevant past history incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
2
1
1
Order By: Relevance
“…Cervical stenosis was found to be one of the risk factors for superficial spreading SCC of the cervix into the endometrium in many studies [ 4 , 5 ], but in the present case, we could not find any stenosis. There are two possible theories for the superficial spread of cervical carcinoma.…”
Section: Discussioncontrasting
confidence: 91%
“…Cervical stenosis was found to be one of the risk factors for superficial spreading SCC of the cervix into the endometrium in many studies [ 4 , 5 ], but in the present case, we could not find any stenosis. There are two possible theories for the superficial spread of cervical carcinoma.…”
Section: Discussioncontrasting
confidence: 91%
“…Astonishingly, we have found that some cases even shared the same characteristics as ours, for example, in a very recent case published in Spain, the 66-year-old patient also underwent cervical conization 15 years ago and had a finding of HSIL, was lost to regular follow-up, and underwent laparoscopic hysterectomy for the symptoms of vaginal discharge after discovering cervical stenosis and pyometra. Her final pathology also revealed HSIL within the cervix and SCC in the endometrium with a depth of 2.8 mm[ 7 ]. Anne Chao et al [ 8 ] also reported a case with fatal pyometra (1200 mL of pus that was cultured Staphylococcus epidermidis) in a 60-year-old patient whose pathology also revealed cervical HSIL that progressed into SCC in the endometrium.…”
Section: Discussionmentioning
confidence: 99%
“…Плоскоклеточный рак эндометрия также регистрируется в пределах 1%, однако отдельным морфотипом данная опухоль не выделена ни в одной из существующих классификаций. Тем не менее, интерес к этому гистотипу эндометриоидной аденокарциномы в последние годы растет и привлекает все большее внимание как зарубежных, так и отечественных исследователей из-за своей агрессивности и высокого опухолевого потенциала [6][7][8].…”
Section: Morphological and Some Immunohistochemical Features Of Diffe...unclassified